Lima Urban Transport : On the Way to Transformation - Darido, Georges (World Bank, Washington, DC, 2016)
The implementation of metro line 2, now under way, will provide a modern, 35 kilometer mass transit axis linking major population and job centers in Lima, the capital of Peru, with Callao to the west, the country’s chief seaport and international airport. Integrated with the Lima-Callao region’s existing public transport network, line 2 will create a major corridor that will improve the accessibility of jobs, services, and markets for 2.3 million people and provide a backbone for more efficient urban development. Beyond the investment loan, this co-financed project is an outgrowth of a long term metropolitan transport strategy and multifaceted engagement that is aligned with the World Bank’s goals of reducing poverty and boosting shared prosperity through sustainable development. It will give a boost to the competitiveness of the entire Lima-Callao Metropolitan Region, which has a population of more than 9 million and constitutes more than one-third of the national economy.